Medical Research Volunteer Program (MRVP): innovative program promoting undergraduate research in the medical field. Issue 1 (December 2016) - Dagher, Michael; Atieh, Jessica; Soubra, Marwa; Khoury, Samia; Tamim, Hani; Kaafarani, Bilal
Abstract Background Most educational institutions lack a structured system that provides undergraduate students with research exposure in the medical field. The objective of this paper is to describe the structure of the Medical Research Volunteer Program (MRVP) which was established at the American University of Beirut, Lebanon, as well as to assess the success of the program. Methods The MRVP is a program that targets undergraduate students interested in becoming involved in the medical research field early on in their academic career. It provides students with an active experience and the opportunity to learn from and support physicians, clinical researchers, basic science researchers and other health professionals. Through this program, students are assigned to researchers and become part of a research team where they observe and aid on a volunteer basis. This paper presents the MRVP's four major pillars: the students, the faculty members, the MRVP committee, and the online portal. Moreover, details of the MRVP process are provided. The success of the program was assessed by carrying out analyses using information gathered from the MRVP participants (both students and faculty). Satisfaction with the program was assessed using a set of questions rated on a Likert scale, ranging from 1 (lowest satisfaction) to 5 (highest satisfaction). Results A total of 211 students applied to the program with a total of 164 matches being completed. Since the beginning of the program, three students have each co-authored a publication in peer-reviewed journals with their respective faculty members. The majority of the students rated the program positively. Of the total number of students who completed the program period, 35.1 % rated the effectiveness of the program with a 5, 54.8 % rated 4, and 8.6 % rated 3. A small number of students gave lower ratings of 2 and 1 (1.1 % and 0.4 %, respectively). Conclusion The MRVP is a program that provides undergraduate students with the opportunity to learn about research firsthand as they volunteer and aid in different research projects. This program also provides faculty members with the help to conduct their research projects and opportunity to influence future generations. It was shown that so far the MRVP has been successful in reaching its goals, for both students and faculty.